Manajemen Mutu Madrasah Diniyah di Era Kontemporer - Nur Jannah (STAIFAS-Press, 2018)
Madrasah Diniyah is one of the very unique Islamic Education institutions, where its existence is an asset that is urgently needed in this contemporary era, the rapid development of technology and communication is not only positive but also affects the moral and spiritual crisis faced by generations current generation of millennials. The existence of the Diniyah Madrasah is expected to be able to make a positive contribution in overcoming the problem, but it is only necessary to implement quality management in the Diniyah Madrasah because in reality there are still many shortcomings in the Islamic Early Madrasas, still impressed as they are and traditional Therefore, it is necessary to improve the quality of the Madrasah Diniyah in this contemporary era. With more professional management, the use of strategies that prioritize creativity is in accordance with the state of society's culture and needs to be supported by various factors, both internal and external so as to provide educational output in the form of generations of millennials who are virtuous, intellectual, skilled and charitable so can contribute to the glory of Islamic civilization, the nation and the State of Indonesia in the present and futureKeyword: Quality Management, Madrasa Diniyah